2017
DOI: 10.1097/gox.0000000000001187
|View full text |Cite
|
Sign up to set email alerts
|

Flap Reconstruction for Pressure Ulcers: An Outcomes Analysis

Abstract: Background:Historically, complication rates after pressure ulcer reconstruction utilizing flap coverage have been high. Patients undergoing operations for pressure ulcer coverage typically have multiple risk factors for postoperative complications. The purpose of this study was to examine a large patient series in the pressure ulcer population to uncover objective evidence of the linkage between risk factors and outcomes after flap coverage.Methods:This study was a retrospective chart review of patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 49 publications
6
84
4
2
Order By: Relevance
“…Most of the wounds in this study were over the ischial tuberosities, which is consistent with previously published literature . This relates to the fact that most paralysed patients spend much of their day sitting in their manual or power wheelchairs, and the seating systems are unfortunately not always optimised.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Most of the wounds in this study were over the ischial tuberosities, which is consistent with previously published literature . This relates to the fact that most paralysed patients spend much of their day sitting in their manual or power wheelchairs, and the seating systems are unfortunately not always optimised.…”
Section: Discussionsupporting
confidence: 89%
“…Most common known predictive factors for complications in pressure ulcer reconstruction are BMI < 18, smoking, osteomyelitis, diabetes, ulcers located over the ischial tuberosity, and a previous reconstruction . In the current study, no correlation was found between complications and BMI, diabetes, or the proportion of patients with multiple wounds.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Unfortunately, despite adequate flap coverage, nearly one-third of patients will develop a recurrent pressure ulcer [4,5] . A history of previous pressure ulcer increases the risk of developing a second pressure ulcer, particularly in the ischial region [1,6] .…”
Section: Introductionmentioning
confidence: 99%